La economía española - Matilde Alonso Pérez; Elíes Furió Blasco (Cahiers de Civilisation Espagnole Contemporaine)
The objective of paper is to analyze the economic situation in Spain, which is currently in the process of moving from a period of growth, into an economic crisis. This recent economic development enabled Spain to make significant advances in terms of personal income. The population increase over recent years, in part thanks to immigration; has translated into an augmentation in the number of households and their requirement for apartments. In addition, good credit conditions favored the expansion of the construction sector. However, these external restrictions on growth and the internal economic bottlenecks, most notably in the construction industry, accompanied by the international crisis, have caused the first Spanish economic crisis of the 21st century.